Study of relative stability of tautomeric forms of phenylbutazone and calculation of UV-Vis and ECD spectra - Souza, A. R. [UNESP]; Ximenes, V. F. [UNESP]; Morgon, N. H. (Brazilian Chemical Soc, 2016)
In this work, a theoretical study was carried out to investigate the electronic structures of the deprotonated form of phenylbutazone. Considering a relaxed PES scan from three selected dihedral angles (delta(1), delta(2), and delta 3) and by the conformational analysis (Boltzmann distribution), at PM3 methodology, eight most important structures were obtained. These structures were optimized and the TD-DFT/PCM (aqueous solvent) at B3LYP/6-31G(d) level and calculations of the UV-Vis and ECD spectra were obtained at CAM-B3LYP/6-311++G(d, p) methodology. Absorption maxima occur at 230 to 250 nm.
Keywords: TD-DFT; Electronic and Molecular Structures; Electronic Circular Dichroism; Phenylbutazone